Narratives of motherhood : voices of selected South African Women. - Van Doorene, Sharon (My University, 2009)
The study explored whether South African mothers subscribed to the Western ideology of intensive motherhood and how this ideology was altered or resisted. Semi-structured interviews were conducted with ten working South African mothers with a child under the age of ten. Thematic content analysis revealed that motherhood was largely regarded as synonymous with womanhood, where the inherent and biological ability to bear children rendered the mother responsible for intensive efforts in child-raising. As a result, motherhood was a gendered practice situated within a powerful and normative ideology of inequality. These themes were discussed in the racially stratified and gendered context of South Africa from a feminist perspective. The research concluded with a recommendation that alternative motherhood ideologies, more representative of the diverse contexts and experiences of mothers, are explored.
Keywords: Motherhood; South Africa